2010
DOI: 10.1097/jgp.0b013e3181d6b68d
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Syndromes in a Large Cohort of Newly Diagnosed, Untreated Patients With Alzheimer Disease

Abstract: The authors' study supports the use of a syndrome approach for neuropsychiatric evaluation in patients with AD. Individual neuropsychiatric symptoms can be reclassified into five distinct psychiatric syndromes. Clinicians should incorporate a thorough psychiatric and neurologic examination of patients with AD and consider therapeutic strategies that focus on psychiatric syndromes, rather than specific individual symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 42 publications
11
146
5
3
Order By: Relevance
“…447 Similarly, a study of newly diagnosed patients with AD found that 78% had neuropsychiatric symptoms and 59% had clinically significant symptoms. 448 As people with mild to moderate dementia may not have any or clinically significant neuropsychiatric symptoms and, therefore, have no potential for these to improve, if the underlying disease is modified, this floor effect means that effective treatments for disease modification would require hugely increased samples size to show a significant effect on neuropsychiatric symptoms.…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%
“…447 Similarly, a study of newly diagnosed patients with AD found that 78% had neuropsychiatric symptoms and 59% had clinically significant symptoms. 448 As people with mild to moderate dementia may not have any or clinically significant neuropsychiatric symptoms and, therefore, have no potential for these to improve, if the underlying disease is modified, this floor effect means that effective treatments for disease modification would require hugely increased samples size to show a significant effect on neuropsychiatric symptoms.…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%
“…Deposition of beta-amyloid plaques and neurofibrillary tangles, the hallmark pathological changes in AD (3), is hypothesized to begin decades before the emergence of cognitive symptoms and subsequent functional decline (4). Emotional symptoms are also common and have been found in 35-85% of patients with MCI (5-7) and up to 75% of patients with AD (8), with depression and anxiety the most frequent symptoms seen. Individuals with MCI who have comorbid emotional complaints are more likely to progress to dementia than those without such symptoms (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…However, a recent study using untreated patients with AD showed that disease severity was correlated with neuropsychiatric abnormalities except the affective syndromes [10]. Moreover, in our study, K-NPI scores were very closely related to general and specific cognitive functions in all groups, including the depression and apathy group (e.g.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have mainly focused on reducing NPI domain factors and thus defining sub-syndromes of AD [5][6][7][8][9][10]. However, our study focused on extracting homogenous groups from numerous NPI domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation